Finding the Best Nursery: How Habitat Features Shape Juvenile Snapper ( Chrysophrys auratus ) Density - Jessica L. Campbell; Richard B. Taylor; Mark A. Morrison (New Zealand Journal of Marine and Freshwater Research, 2026)
This study examines habitat preferences of juvenile Australasian snapper ( Chrysophrys auratus ) in northeastern New Zealand, analysing data from 113 stations across structured and unstructured habitats. We investigated how juvenile snapper densities were influenced by environmental factors, including prey availability and physical habitat features. Seagrass supported significantly higher snapper densities than all other habitats, with mean densities more than 80 times greater than non‐seagrass habitats, reinforcing its role as a key nursery habitat. Regression analyses identified seagrass presence as the strongest predictor of density, with benthic productivity and plankton flux also weakly correlated when considering all habitats together. In non‐seagrass environments, there were weak trends for densities to be higher in shallow water and in the presence of burrows. Current speed also appeared to play a role, potentially modifying prey availability and interacting with habitat structure. These findings provide new insights into why seagrass meadows are particularly beneficial for juvenile snapper, reinforcing the need for targeted conservation and restoration efforts to sustain nursery habitats and support snapper populations.